The role of lean management in achieving institutional excellence An Empirical Study: Asir Central Hospital in Abha - AlDoshan, Neamah Adel (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to determine the role of lean management in achieving institutional excellence in Asir Central Hospital in Abha city. The researcher relied on the descriptive analytical approach and used the questionnaire as a tool for collecting information and data from the study community, which is represented by the (2192) employees of Asir Central Hospital, and (492) questionnaires were retrieved. Among the most important findings of the study: The results of the analysis confirmed the noticeable effects achieved by the administration of Asir Central Hospital in some important aspects through its application of lean management approach, such as leadership excellence, where the impact percentage reached 94.2%, as well as with regards to the human resources excellence variable, where the percentage reached 91.5%. The results of the study showed the tireless pursuit of Asir Hospital to support the applications of lean management by giving it a high priority for the continuous improvement of the services provided by the hospital. Among the most important recommendations made by the researcher are: The hospital management should provide more international courses and programs on the requirements for activating lean management and its great role in institutional excellence for hospitals, the necessity for the Kingdom’s hospitals in general and Asir Central Hospital, in particular, to spread the culture of waste reduction for its effective role in institutional excellence in order to get rid of any unnecessary procedures.
Keywords: Administration; Lean Management; Tools of Lean Management; Institutional Excellence